The practice of reading : interpreting the novel - Alsop, Derek, 1960-; Walsh, Chris (New York : St. Martin's Press, 1999)
This book is about: Reading and Interpretation; The role of the reader; The process of reading; ...
Keywords: English fiction; Books and reading; History and criticism; English fiction -- History and criticism; Books and reading